Permasalahan dan Upaya Pengembangan Kajian Islam Multidisipliner di Pascasarjana Universitas Islam Negeri (UIN) Sunan Ampel Surabaya - Khoirun Niam; Masdar Hilmy (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2019)
The transformation of IAIN Sunan Ampel Surabaya to UIN Sunan Ampel Surabaya has an impact on changing the epistemology of science. The choice of twin towers as the paradigm needs to be translated to various levels of academic practice, so that the persons of academic community in UIN Sunan Ampel can understand and implement the paradigm. The studies in UIN Sunan Ampel also must be oriented to the paradigm. One of them is in Postgraduate Program, which seeks to develop inter, multi and trans-disciplinary Islamic studies at the level of PhD program. This study found that (1) most of the Stakeholders Postgraduate Program of UIN Sunan Ampel Surabaya have good understanding of inter and multidisciplinary Islamic studies; (2) the problems in implementing the inter and multidisciplinary Islamic studies are in four aspects: aspects of students, aspects of lecturers, aspects of curriculum, and aspects of carrying capacity and policies.